Attitude, Islamic Tourist Satisfaction dan Destination Loyalty: Dasar untuk Mengembangkan Halal Tourism DiKota Bukittinggi - Primalita, Ratni (Manajemen dan Kewirausahaan; Vol 10 No 3 (2019): Published in September 27th, 2019DO - 10.31317/jmk.10.3.1-14.2019, 2019)
Halal tourism is the goverment’s concern to develop tourism in the city of Bukittinggi. Therefor, efforts need to be made to increase the destination loyalty through the islamic tourism satisfaction. This study discusses the influence of attitudes on islamic tourist satisfaction and the influence of islamic tourist satisfaction on destination loyalty in the city of Bukittinggi. This type of research is explanatory research. The sampling technique is convenience sampling with a sample size of 100 archipelago tourists. Respondent collected directly at tourist destinations in the city of Bukittinggi. Time horizon is a cross section, which is data collected at one time in 2018. Data analysis tools use descriptive statistics and structural equation model (SEM). The results showed the there was a significant and positive influence of attitude variables on the islamic tourist satisfaction, and the influence of islamic tourist satisfaction on destination loyalty